2018
DOI: 10.1186/s40478-018-0600-7
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegeneration in SCA14 is associated with increased PKCγ kinase activity, mislocalization and aggregation

Abstract: Spinocerebellar ataxia type 14 (SCA14) is a subtype of the autosomal dominant cerebellar ataxias that is characterized by slowly progressive cerebellar dysfunction and neurodegeneration. SCA14 is caused by mutations in the PRKCG gene, encoding protein kinase C gamma (PKCγ). Despite the identification of 40 distinct disease-causing mutations in PRKCG, the pathological mechanisms underlying SCA14 remain poorly understood. Here we report the molecular neuropathology of SCA14 in post-mortem cerebellum and in human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
62
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(72 citation statements)
references
References 46 publications
8
62
1
1
Order By: Relevance
“…There are now >40 different missense mutations or deletions which have been found in human SCA14 patients ( Chelban et al, 2018 ; Wong et al, 2018 ) ( Fig. 1 A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are now >40 different missense mutations or deletions which have been found in human SCA14 patients ( Chelban et al, 2018 ; Wong et al, 2018 ) ( Fig. 1 A ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, other SCA14 mutations, especially in the C1 domain, are functionally defective because of decreased binding to diacylglycerol pointing toward a loss of function phenotype ( Verbeek et al, 2008 ). These findings suggest that pathology in SCA14 is not simply because of one single mechanism but rather the result of complex mechanisms involving dysregulation of PKCγ ( Shimobayashi and Kapfhammer, 2018 ; Wong et al, 2018 ).…”
Section: Introductionmentioning
confidence: 94%
“…The rapid development in the iPSC field and the potential of iPSC to differentiate into different cell types not only offer great opportunities to study the pathogenesis of neurodegenerative diseases including SCA3 but also provide a platform to identify new therapeutic strategies [2831]. In the past decade, neuronal cells derived from patient-specific iPSCs have been generated to model neurodegenerative diseases such as PD [32, 33], Alzheimer's disease (AD) [34, 35], and HD [36, 37], and relatively handful iPSC studies focused on cerebellar ataxias including Friedreich's ataxia (FRDA) [3843] and SCAs: SCA2 [44], SCA3 [4548], SCA6 [49], SCA7 [50], SCA14 [51], and SCA36 [52]. Koch et al first reported that L-glutamate-induced excitation of SCA3-iPSC-derived neurons initiated calpain-dependent proteolysis of ATXN3 followed by the formation of SDS-insoluble aggregates [46].…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal increase in sustained cytosolic Ca 2+ by TRPC5 activation causes neuronal damage through the calpain-caspase-dependent pathway and the CaM kinase as seen in HD (Hong et al, 2015 ). Spinocerebellar ataxia type 14 (SCA14) is an autosomal dominant ND caused by a mutation in protein kinase Cγ (Wong et al, 2018 ). This mutation of SCA14 has been demonstrated to cause phosphorylation failure in TRPC3 channels, resulting in persistent Ca 2+ entry that may contribute to neurodegeneration (Adachi et al, 2008 ).…”
Section: Brain Disordersmentioning
confidence: 99%